Regional Income Inequalities In Poland And Italy - Jędrzejczak, Alina (Comparative Economic Research. Central and Eastern Europe, 2015)
Reducing regional inequality was one of the key means of promoting the “harmonious development” within Europe envisioned in the EEC Treaty of 1957. The pursuit of “economic, social and territorial cohesion” through ever closer regional and national harmonisation was also proclaimed in the 2007 Lisbon Treaty, but deepening European integration has not always been matched with convergence in living standards between sub-national regions. The gap between poorer and richer areas increased during the last economic crisis even in some developed economies, and the income discrepancy between richer and poorer regions is likely to widen further as government-spending cuts disproportionately hurt less prosperous regions. Regional inequalities can be measured in many ways - the extent of inequality may be mapped in terms of demography, income and wealth, labour markets, and education and skills. The main objective of this presentation is to analyse regional inequalities in terms of household income distribution. The empirical evidence comes from the GUS, Istat and Bank of Italy databases and has been analysed by means of inequality and poverty indices calculated at NUTS 1 and NUTS 2 levels. In order to work out the intra-regional and inter-regional contributions to the overall inequality, the Gini index decomposition has been applied. While presenting similar levels of income concentration, Poland and Italy turned out to follow different regional inequality patterns.